2021
DOI: 10.1002/anie.202108818
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Carbochlorocarbonylation of Unsaturated Hydrocarbons via C−COCl Bond Cleavage**

Abstract: Here we report ap alladium-catalysed difunctionalisation of unsaturated CÀCb onds with acid chlorides.F ormally,t he C À COCl bond of an acid chloride is cleaved and added, with complete atom economy,a cross either strained alkenes or atethered alkyne to generate new acid chlorides.The transformation does not require exogenous carbon monoxide, operates under mild conditions,shows agood functional group tolerance,a nd gives the isolated products with excellent stereoselectivity.T he intermolecular reaction tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 153 publications
0
19
0
Order By: Relevance
“…Dong and co-workers recently reported that it is possible to add a C–C bond in a simple cyclic ketone across ethylene or alkynes in the presence of a catalytic amount of a rhodium catalyst and 2-aminopyridine, the latter of which acts as a transient directing group . During the preparation of this Communication, Morandi and co-workers reported the palladium-catalyzed addition of a C–C bond in an acid chloride to norbornene derivatives . Here we report the development of the nickel-catalyzed addition reaction of a C–C bond in aryl amide derivatives across norbornene .…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Dong and co-workers recently reported that it is possible to add a C–C bond in a simple cyclic ketone across ethylene or alkynes in the presence of a catalytic amount of a rhodium catalyst and 2-aminopyridine, the latter of which acts as a transient directing group . During the preparation of this Communication, Morandi and co-workers reported the palladium-catalyzed addition of a C–C bond in an acid chloride to norbornene derivatives . Here we report the development of the nickel-catalyzed addition reaction of a C–C bond in aryl amide derivatives across norbornene .…”
mentioning
confidence: 81%
“…7 During the preparation of this Communication, Morandi and coworkers reported the palladium-catalyzed addition of a C−C bond in an acid chloride to norbornene derivatives. 8 Here we report the development of the nickel-catalyzed addition reaction of a C−C bond in aryl amide derivatives across norbornene. 9 Neither ring strain nor directing groups are required for the C−C bond activation to proceed.…”
mentioning
confidence: 99%
“…In recent years, shuttle catalysis has emerged as a useful tool for the introduction of important synthetic functional groups by circumventing the need for directly using toxic and hazardous reagents, such as HMgBr, HCN, CO, HCl, , HI, , Cl 2 , and Br 2 in a transfer process. Using this paradigm, a reversible HCN-free transfer hydrocyanation strategy has been developed by our group .…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, an atom-economical decarbonylative alkylation of acid chlorides has also been achieved via the difunctionalization of unsaturated hydrocarbons. 12 Given that these aroyl derivatives require tedious preparation using carboxylic acids, a more direct in situ activation strategy of general carboxylic acids has emerged towards the decarbonylative C–C bond formation in recent years. 7 c , h ,13–15 We envision that the imitation of such a strategy may cater for the high demand and endless chase towards efficient methylation methods.…”
mentioning
confidence: 99%